Decaffeinated green tea extract as a nature-derived antibiotic alternative: An application in antibacterial nano-thin coating on medical implants. (30th July 2022) - Park, Jihyo; Chi, Lianhua; Kwon, Hee-Young; Lee, Jisoo; Kim, Seunghwi; Hong, Seonki
Graphical abstract: Highlights: Decaffeination allowed the enrichment of antibacterial components from green tea extract. The coating with decaffeinated green tea extract showed a potent as a powerful antibacterial material both in vitro and in vivo. The coating was successfully applied on a variety of substrates which showed its versatility. Nature-derived coating can be an alternative to antibiotics currently used in clinical settings. Abstract: Plant-derived polyphenols have emerged as molecular building blocks for biomedical architectures. However, the isolation of polyphenols from other components requires labor-intensive procedures, which increases costs and often raises environmental concerns. Here, we suggest that decaffeination can be a convenient and cost-effective method for enhancing the antibacterial performance of polyphenol-rich tea extracts. As a demonstration, we compared the properties of a nano-thin coating made of decaffeinated (dGT coating) and raw green tea extract (GT coating). The dGT coating exhibited enhanced antibacterial performance with regard to bacterial killing and prevention of bacterial attachment compared with the GT coating. Moreover, the chemical reactivity of the dGT coating was further utilized for secondary modifications, which enhanced the overall antibacterial performance of the modified surface. Given its intrinsic low toxicity, we envision that the developed antibacterial coating is ready for the next steps toward application in real clinical settings.